Investigation into The Effect of Arabic Incompetence on The Students’ Performance in Islamic Studies in Ibadan South-East Of Oyo State In Nigeria - Kazeem Adekunle Adegoke (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2016)
Abstract This study investigated the effect of incompetence in Arabic language on students’ performances in Islamic studies in the selected senior secondary schools in Ibadan South-East Local Government Area of Oyo State, Nigeria. The main objective of this study was to ascertain the argument that the poor performance of senior secondary students in Islamic studies is as a result of incompetence and non-proficiency in Arabic language on the side of learners and teachers. The methodology employed in this study was the quantitative approach. Location of the study was Ibadan South-East Local Government Area of Oyo State. Teachers of Islamic studies and students were randomly selected using the stratified random sampling technique from six senior secondary schools. The data gathered were analysed using simple percentages and chi-square statistical analysis. The findings revealed that significant number of students in Senior Secondary School’s poor performance in Islamic studies was due to their incompetence in Arabic as a result of their lack of exposure to the Arabic language and their poor background in Arabic from the previous classes. It also revealed that some of their teachers in Islamic studies were not competent in Arabic reading and writing. Abstrak Penelitian ini menginvestigasi efek ketidakmampuan bahasa Arab terhadap kinerja siswa studi Islam di sekolah-sekolah menengah atas terpilih di Ibadan Tenggara, di Area Pemerintahan Daerah Negara Oyo, Nigeria. Tujuan utama penelitian ini untuk menegaskan argumen bahwa buruknya kinerja siswa sekolah menengah atas pada studi Islam adalah akibat dari ketidakmampuan dan ketidakmahiran bahasa Arab pada peserta didik dan guru. Metode penelitian pendekatan kuantitatif. Lokasi penelitian adalah di Area Pemerintah Daerah Ibadan Tenggara Negara Oyo. Guru dan siswa program studi Islam dipilih secara acak menggunakan teknik stratified random sampling dari enam sekolah menengah atas. Data yang terkumpul dianalisis dengan menggunakan persentase sederhana dan analisis statistik chi-square. Hasil penelitian menunjukkan buruknya kinerja sebagian besar siswa sekolah menengah atas studi Islam adalah karena ketidakmampuan mereka dalam bahasa Arab sebagai akibat dari kurangnya eksposisi terhadap bahasa Arab dan kurangnya latar belakang bahasa Arab mereka dari kelas sebelumnya. Penelitian ini juga mengungkapkan bahwa beberapa guru mereka pada program studi Islam tidak kompeten dalam membaca dan menulis bahasa Arab. How to Cite : Kazeem Adekunle Adegoke. (2016). Investigation into The Effect of Arabic Incompetence on The Students’ Performance in Islamic Studies in Ibadan South-East Of Oyo State In Nigeria. TARBIYA: Journal Of Education In Muslim Society, 3(1), 20-31. doi:10.15408/tjems.v3i1.3374. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v3i1.3374